FSP and FLTL framework for specification and verification of middle-agents - Bădică, Amelia; Bădică, Costin (Zielona Góra: Uniwersytet Zielonogórski)
Agents are a useful abstraction frequently employed as a basic building block in modeling service, information and resource sharing in global environments. The connecting of requester with provider agents requires the use of specialized agents known as middle-agents. In this paper, we propose a formal framework intended to precisely characterize types of middle-agents with a special focus on matchmakers, brokers and front-agents by formally modeling their interactions with requesters and providers. Our approach is based on capturing interaction protocols between requesters, providers and middle-agents as finite state processes represented using FSP process algebra
Keywords: multi-agent system; interaction protocol; process algebra; formal specification